2020
DOI: 10.1097/prs.0000000000007440
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Nonoperative Treatments for Lateral Epicondylitis: A Systematic Review and Meta-Analysis

Abstract: Background: Lateral epicondylitis is a common overuse injury affecting approximately 1 to 3 percent of the population. Although symptoms may disappear spontaneously within 1 year, the clinical guidelines for conservative treatment are not clear. The authors’ objective was to examine the outcomes of nonsurgical treatments for lateral epicondylitis through a meta-analysis and provide a treatment recommendation using the available evidence. Methods: The au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 82 publications
2
30
0
1
Order By: Relevance
“…The findings of the present study are consistent with a recent systematic review and meta-analysis of RCTs by Kim et al that compared nonoperative treatment in lateral epicondylitis. 18 The latter study found that injections did not improve patient-reported outcomes. Our findings indicate that both pain and function were statistically worse in the CSI group.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The findings of the present study are consistent with a recent systematic review and meta-analysis of RCTs by Kim et al that compared nonoperative treatment in lateral epicondylitis. 18 The latter study found that injections did not improve patient-reported outcomes. Our findings indicate that both pain and function were statistically worse in the CSI group.…”
Section: Discussionmentioning
confidence: 94%
“… 16 In contrast, a recent meta-analysis reported that injections did not confer any treatment benefits compared with placebo, whereas physiotherapy improved pain and functional scores. 18 A meta-analysis by Weber et al concluded that there was insufficient evidence to support physiotherapy for the treatment of tennis elbow. 39 These inconsistent findings make interpretation of the literature difficult and cloud clinicians’ ability to counsel patients effectively.…”
mentioning
confidence: 99%
“…In a recent meta-analysis, a conclusion that injection therapy did not improve pain and functional outcomes but increased risk of adverse events in LET has been made without including DPT in the analysis. 27 Therefore, we conducted this systematic review of randomized control trials (RCTs) to assess and analyze the effectiveness of DPT in LET.…”
Section: Introductionmentioning
confidence: 99%
“…Lateral epicondylitis is a common overuse injury affecting approximately 1 to 3 percent of the population [2]. The typical…”
Section: Introductionmentioning
confidence: 99%